2014
DOI: 10.1016/j.plantsci.2013.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Induction of phytic acid synthesis by abscisic acid in suspension-cultured cells of rice

Abstract: A pathway of phytic acid (PA) synthesis in plants has been revealed via investigations of low phytic acid mutants. However, the regulation of this pathway is not well understood because it is difficult to control the environments of cells in the seeds, where PA is mainly synthesized. We modified a rice suspension culture system in order to study the regulation of PA synthesis. Rice cells cultured with abscisic acid (ABA) accumulate PA at higher levels than cells cultured without ABA, and PA accumulation levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…Overall, our studies indicated that some of the PA pathway genes are highly induced by ABA when compared to GA 3 . These observations are in accordance with the previous observations reported from rice suspension cells where overall induction of PA biosynthesis genes was observed in presence of ABA [ 14 ]. Altogether, our observations also support that, ABA and GA 3 act antagonistically in developing wheat grains.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…Overall, our studies indicated that some of the PA pathway genes are highly induced by ABA when compared to GA 3 . These observations are in accordance with the previous observations reported from rice suspension cells where overall induction of PA biosynthesis genes was observed in presence of ABA [ 14 ]. Altogether, our observations also support that, ABA and GA 3 act antagonistically in developing wheat grains.…”
Section: Discussionsupporting
confidence: 94%
“…In ABA treated wheat seeds, the expression of TaIPK2 was consistently up-regulated at all time points which are in contrast to the expression of AtIPK2β that decreased upon ABA treatment [ 54 ]. Expression pattern of OsIPK1 [ 14 ], and our results regarding TaIPK1 suggested higher fold accumulation of their transcripts when treated with ABA. Except for TaITPK2 and TaIMP all the wheat genes involved in PA biosynthesis were induced by ABA ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations